Human intention detection with facial expressions using video analytics - Prema, K; Leema Priyadharshini, L; Shyamala Kumari, C; Florence, S (International Journal of Engineering and Technology, 2018)
The manuscript should contain an abstract. The abstract should be self-contained and citation-free and should not exceed 200 words. The abstract should state the purpose, approach, results and conclusions of the work.The author should assume that the reader has some knowledge of the subject but has not read the paper. Thus, the abstract should be intelligible and complete in it-self (no numerical references); it should not cite figures, tables, or sections of the paper. The abstract should be written using third person instead of first person.